El arzobispado de Compostela, los obispados del noroeste de la península ibérica y el IV Concilio de Letrán de 1215 - Domínguez Sánchez, Santiago (2017)
This paper critically examines and analyzes the participation of the bishops of the Northwest Spain in the Fourth Lateran Council of 1215, whose eighth centenary is now celebrated. The article details the gradual implementation in this territory of six council provisions: first, the question of the primacy of the Hispanic Church, especially with the struggles between the archbishops of Toledo and Compostela, and also, the imposition of greater control in ecclesiastical discipline, the various requirements for improving a stronger piety of the faithful, a new regulation of the sacrament of marriage, certain measures taken in relation to the Jews and, finally, the call and appeal for the Crusade.
En este artículo se estudia y analiza críticamente la participación de los obispos del noroeste de la península ibérica en el IV Concilio de Letrán del año 1215, cuyo octavo centenario se celebra ahora. Se hace un pequeño repaso a la aplicación paulatina en este territorio de seis decisiones conciliares: la primera, el problema de la primacía de la Iglesia hispana, especialmente con las luchas entre los arzobispos de Toledo y Compostela, así como la imposición de un mayor control en la disciplina eclesiástica, las diversas disposiciones para la mejora de la vida de piedad de los fieles, una nueva regulación del sacramento del matrimonio, las medidas tomadas en relación con los judíos y el llamamiento a la cruzada.